Addressing SITU_ACCÃO: Case Study of an Artistic Intervention and Research into Public Spaces - Pratas-Cruzeiro, Cristina; Elias, Helena; Valente, Catarina; Cortez, Tânia (Arte, Individuo y Sociedad, 2021)
This article explores the embodiment of the art historical avant-garde legacy through some of the artistic manifestations across the 20th century, in public spaces. At the same time, it discusses the incorporation of such historical background in contemporary collaborative research practices. It does so by addressing the case study of the collective Situ_Acção, a group of artists and researchers from different fields of arts and communication, whose activity is focused on intervention in the city, based on action and collaborative research and shared reflection on urban phenomena, associated with public arts. First, it will be described how Situ_Acção started a common ground for the inquiry: the legacy of urban murals in Lisbon. By investigating the Portuguese digital archives of urban murals of the 1970s and 1980s, Situ_Acção applied spatial artistic techniques to overcome the missing information regarding the places of intervention. In addition, the use of performance and on-site installation implements alternative approaches to communicate research to a wider audience. This exercise will allow different degrees of participation within the work of art in progress. The project Memory in the Walls (MOWS) will be described in the concluding chapter, in order to explore such degrees of interaction.